Does Leveling the Upper Thoracic Spine Have Any Impact on Postoperative Clinical Shoulder Balance in Lenke 1 and 2 Patients?. Issue 14 (15th July 2016) - Amir, Dzulkarnain; Yaszay, Burt; Bartley, Carrie E.; Bastrom, Tracey P.; Newton, Peter O.
Abstract : Study Design: Retrospective review of prospective data. Objective: To determine if surgically leveling the upper thoracic spine in patients with adolescent idiopathic scoliosis results in level shoulders postoperatively. Summary of Background Data: Research has shown that preoperatively tilted proximal ribs and T1 tilt are more correlated with trapezial prominence than with clavicle angle. Methods: Prospectively collected Lenke 1 and 2 cases from a single center were reviewed. Clinical shoulder imbalance was measured from 2-year postoperative clinical photos. Lateral shoulder imbalance was assessed utilizing clavicle angle. Medial imbalance was assessed with trapezial angle (TA), and trapezial area ratio (TAR). First rib angle, T1 tilt, and upper thoracic curve were measured from 2-year radiographs. Angular measurements were considered level if ⩽ 3° of zero. TAR was considered level if ⩽ 1 standard deviation of the natural log of the ratio. Upper thoracic Cobb at 2-years was categorized as at or below the mean value (⩽ 14°) versus above the mean. Results: Eighty-four patients were identified. There was no significant difference in the percentage of patients with a level clavicle angle or TAR based on first rib being level, T1 tilt being level, or upper thoracic Cobb being at/below versus above the mean ( P  < 0.05). There was a significant difference in the proportion of patients with level TA based on first rib angle ( P  = 0.006), T1 tilt ( P  ⩽ 0.001), and postoperative upper thoracic Cobb ( P  = 0.04). The odds ratios of having a level TA were 3.9 (1.4–10.6) if first rib was level, 5 (1.9–12.9) if T1 tilt was level, and 2.6 (1.0–6.3) if postoperative upper thoracic Cobb was ⩽ 14°. Conclusion: Leveling the upper thoracic spine does not guarantee clinically balanced shoulders or clavicles. Trapezial prominence was impacted by leveling T1 and the first rib and by minimizing the upper thoracic curve. How to achieve laterally balanced shoulders postoperatively remains unclear. Level of Evidence: 3